Do more people recover from chronic fatigue syndrome with cognitive behaviour therapy or graded exercise therapy than with other treatments?. Issue 1 (2nd January 2017) - Sharpe, M.; Chalder, T.; Johnson, A. L.; Goldsmith, K. A.; White, P. D.
ABSTRACT: Background: Wilshire et al. suggest that we have overestimated the number of patients that recover from chronic fatigue syndrome (CFS) after receiving a course of either cognitive behaviour therapy (CBT) or graded exercise therapy (GET), as reported in a secondary analysis of outcome data from the Pacing, graded Activity and Cognitive behavior therapy; a randomized Evaluation (PACE) trial. We provide counter-arguments to this view. Purpose: To provide an alternative view to that offered by Wilshire et al. Methods: We review the two different analyses of PACE trial outcome data to estimate recovery, and compare these to other published trials and cohort studies. Results: While there is no gold standard for recovery from CFS, previous trials and cohort studies provide support for our analysis of recovery in the PACE trial. Our finding that 22% of participants recover from the current episode of CFS after either CBT or GET, compared to 8% after adaptive pacing therapy and 7% after specialist medical care alone, is consistent with the literature. Conclusions: Our original conclusions that ' … recovery from CFS is possible, and that CBT and GET are the therapies most likely to lead to recovery' is an important, reasonable, and hopeful message for both clinicians and patients.